Green energy and content-aware data transmissions in maritime wireless communication networks - Yang, Tingting (2015)
In this paper, we investigate the network throughput and energy sustainability of green-energy-powered maritime wireless communication networks. Specifically, we study how to optimize the schedule of data traffic tasks to maximize the network throughput with Worldwide Interoperability for Microwave Access (WiMAX) technology. To this end, we formulate it as an optimization problem to maximize weight of the total delivered data packets, while ensuring that harvested energy can successfully support transmission tasks. The formulated energy and content aware vessel throughput maximize problem (EVTMP) is proved to be NP-complete. We propose a green energy and content aware data transmission framework that incorporates the energy limitation of both infostations and Delay Tolerant Network (DTN) throw-boxes. The green energy buffer is modeled G=G=1 queue, and two heuristic algorithms are designed to optimize the transmission throughput and energy sustainability. Extensive simulations demonstrate that our proposed algorithms can provide simple yet efficient solutions in a maritime wireless communication network with sustainable energy.